2003
DOI: 10.1159/000069485
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Peripartum Factors on the Onset and Duration of Lactation

Abstract: Knowledge of peripartum indicators of those mother-infant pairs that are at increased risk of early failure of lactation may improve specific support of breastfeeding. Mode of delivery, labor complications, hyperbilirubinemia, milk intake and weight development were evaluated in healthy term infants in a hospital (n = 338). Delayed onset of lactation was observed in primiparae and in study participants with peripartum complications. The quantitative intake of human milk, assessed by test weighing 0–24 h and 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 24 publications
3
30
0
4
Order By: Relevance
“…12 It has been demonstrated that although peripartum factors may contribute to early lactation failure, long-term success of breastfeeding was predominantly determined outside the hospital. 13 Our participants were generally well supported after discharge with 85% expecting at least an adult to be available at home to assist. In our newly urbanized community, new mothers often returned to their hometowns for confinement and to get support from their own mothers.…”
Section: Discussionmentioning
confidence: 84%
“…12 It has been demonstrated that although peripartum factors may contribute to early lactation failure, long-term success of breastfeeding was predominantly determined outside the hospital. 13 Our participants were generally well supported after discharge with 85% expecting at least an adult to be available at home to assist. In our newly urbanized community, new mothers often returned to their hometowns for confinement and to get support from their own mothers.…”
Section: Discussionmentioning
confidence: 84%
“…Attempts were made to contact authors from 39 studies for additional data (6,7,10,; 36 replied, providing data previously unpublished in this form from 245,455 subjects. Six authors could not provide data (47,48,57,(59)(60)(61) and one author (33) referred us to another publication, but this study was not suitable for inclusion (67). The full text was unobtainable for 3 studies (68)(69)(70).…”
Section: Resultsmentioning
confidence: 99%
“…20 Early initiation of milk expression and frequent milk removal are important factors in the development of an adequate milk supply in this population. [6][7][8] One pilot study demonstrated that initiating milk expression within the first hour after birth is more effective than expressing between 2 and 6 hours.…”
Section: Discussionmentioning
confidence: 99%